Emotional exhaustion and job satisfaction: an investigation of the mediating role of job involvement using structural equation modeling - Allam, Zafrul; George, Shaju; Yahia, Karim Ben; Malik, Azam (International Journal of Innovative Research and Scientific Studies, 2023)
It is important for management to make its employees fully satisfied at work by reducing emotional exhaustion and increasing their involvement. Today the majority of companies strive to improve their employees’ performance by providing them with all the facilities they need to maintain their physical and psychological well-being and thereby enhance their effectiveness. Therefore, the current study aims to examine whether job involvement mediates the relationship between emotional exhaustion and job satisfaction among financial sector employees. An analysis of 200 responses from financial sector employees was conducted using a survey. To gather information, a set of tools including emotional exhaustion, job satisfaction, job involvement and biographical information from bank employees were used. A structural equation model was used to analyze the relationships. The results showed a positive correlation between emotional exhaustion and job involvement between emotional exhaustion and job satisfaction and between job involvement and job satisfaction. Thus, it is observed that job involvement mediates and has a significant impact on job satisfaction. The current findings have their own significance for social scientists and managers since they provide a framework for designing work arrangements in a way to prevent emotional exhaustion while increasing employees’ level of job involvement and job satisfaction. The study concludes with a discussion of limitations and suggestions for future research.